Efektivitas Hybrid e-Learning Mata Kuliah Kimia Klinik dan Bioanalisis di Fakultas Farmasi, Universitas Gadjah Mada - Adam Hermawan; Muthi Ikawati; Susi Ari Kristina; Edy Meiyanto (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The e-learning method has emerged over the years along with the development of information technology. One of the advantages of this method is not depending on space and time of lecture. The course of clinical chemistry and bioanalysis consisting of lectures and practical courses has time and place limitations for practical and discussion between lecturers and students, therefore learning method innovation is needed. This study aimed to evaluate the effectiveness of the hybrid e-learning method using eLisa on student, as well as understanding and evaluating student perceptions and acceptance of the hybrid e-learning method in clinical chemistry and bioanalysis courses. The platform for the the hybrid e-learning method is eLisa (elisa.ugm.ac.id), developed by the Center for Innovation and Academic Studies (PIKA) UGM. A total of 54 UGM Pharmacy students in the sixth semester of the academic year 2017/2018 participated in this learning activity. Online discussion was conducted on a scientific paper or data obtained from practical courses. Lecturers also provide assignments and online quizzes through eLisa every 2 to 3 weeks. Online assignments and quizzes are opened 24 hours after the lectures. The hybrid e-learning method improve student’s understanding on the lectures and results in the increased number of students who get A marks by 100% compared to conventional learning methods. Most students were satisfied and able to enjoy the learning process with hybrid e-learning with eLisa. This method is able to improve the understanding of subjects and students are satisfied with the implementation of course learning. Further development on improving e-learning methods is needed to improve the quality of learning outcomes.